Produced by Sun, Wind or Water: Visions of Renewable Energy in the West German Electricity Industry’s Advertising During the 1980s - Lisanne Rother (Global Environment)
‘Electricity from sun, wind, and water. How much is possible?’, asks an advertisement by the electricity industries’ public relations network Informationszentrale der Elektrizitätswirtschaft during the conflictual environmental protection and anti-nuclear power debates of the 1980s. As the slogan indicates, renewable energy and the transformation of energy systems became an image-relevant factor for the West German electricity industry. Therefore, this article focuses on the visual negotiation and the images publicly promoted by this specific interest group, represented by the Rheinisch-Westfälische Elektrizitätswerke (RWE) and the Informationszentrale der Elektrizitätswirtschaft (IZE). The article explores how and why they shaped specific visions about contemporary and future energy provision. Following visual history’s social constructivist approach, the paper argues that image advertisements by RWE and IZE performatively produced visions of renewable, sustainable energy.